2011
DOI: 10.1111/j.1365-2753.2011.01665.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists contribute to the improved efficiency of medical practices in the outpatient cancer chemotherapy clinic

Abstract: Pharmacists contributed to the improved efficiency of medical practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 21 publications
2
55
0
4
Order By: Relevance
“…A recent study reported that it was an independent risk factor for inhospital mortality in HCAP patients (22). The number of outpatients undergoing cancer therapy is increasing as a result of dramatic advances in cancer treatment and care (23). Therefore, we should recognize malignancy as a risk factor for mortality in patients with pneumonia, excluding those with HAP.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that it was an independent risk factor for inhospital mortality in HCAP patients (22). The number of outpatients undergoing cancer therapy is increasing as a result of dramatic advances in cancer treatment and care (23). Therefore, we should recognize malignancy as a risk factor for mortality in patients with pneumonia, excluding those with HAP.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies had also described the impact of clinical pharmacy services on improving patient care and education (McKee et al, 2011;Valgus et al, 2011;Lihara et al, 2012;Tuffaha et al, 2012). However, patients' informational needs from pharmacists have not been fully studied.…”
Section: Hk Chan and S Ismailmentioning
confidence: 99%
“…55 Most recent reports show how pharmacist interventions help to reduce costs of antiemetics by 16% in outpatient clinics. 57,58 The release of such neurokinin-1 receptor antagonists as aprepitant add to the CINV regimens, especially in patients receiving multiday chemotherapy and cisplatin therapy. The correct utilization of aprepitant has been demonstrated in solid and hematological tumors, for transplant by pharmacists as a supportive regimen.…”
Section: Administrationmentioning
confidence: 99%